PENGARUH LOKASI DAN SERVICESCAPE TERHADAP KEPUASAN KONSUMEN DI HOTEL BINTANG BALI RESORT - Ni Komang Tri Utami Dewi; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
Customer satisfaction is the goal of all companies and business people. In achieving a customer satisfaction, the company always tries to choose the location and provide the best servicecape. The purpose of the study was to determine how the influence of location and servicescape on customer satisfaction at the Bintang Bali Resort Hotel. This research is motivated by the occupancy rate at the Bintang Bali Resort Hotel which fluctuates every year and the complaints found in guest comments on the Hotel Bintang Bali Resort website and also in reviews from Online Travel Agents. The population in this study are all consumers who have stayed at the Bintang Bali Resort Hotel. The number of samples in this study were 85 respondents who were determined based on the purposive sampling method. The data analysis technique used is multiple linear regression analysis. The results of the study show that (1) location has a positive and significant effect on customer satisfaction at the Bintang Bali Resort Hotel, it shows that the more strategic the location, the higher the customer satisfaction. (2) servicescape has a positive and significant effect on customer satisfaction at the Bintang Bali Resort Hotel, it shows that the more servicescape is perceived in accordance with consumer expectations, the more satisfied consumers will be.